Animal Biomonitoring for the Surveillance of Environment Affected by the Presence of Slight Contamination by β-HCH - Alessio Bocedi; Olga Lai; Giada Cattani; Cristina Roncoroni; Giorgia Gambardella; Sara Notari; Francesco Tancredi; Giuseppe Bitonti; Serena Calabrò; Giorgio Ricci (MDPI AG, 2022)
The aim of this study was to evaluate the influence of hidden environmental pollution on some blood parameters of sheep to detect susceptible biomarkers able to reveal slight contamination. Four dairy sheep farms, two with semi-extensive and two with intensive type systems were involved in this study. Two farms in different systems were chosen as properly located in a southern area of Latium (Italy), close to the Sacco River, in which contamination with β-hexachlorocyclohexane (β-HCH) occurred in the past due to industrial waste. A recent study established the presence of low but detectable residual contamination in these areas. The other two farms were outside the contaminated area. Erythrocyte glutathione transferase (e-GST) and oxidative stress parameters were monitored as well as some immune response and metabolic profile parameters throughout the investigated period of four months. The present study showed a relevant and significant increase in e-GST (+63%) in the extensive farming system of the contaminated area, whereas some immune response biomarkers, i.e., white blood cells, neutrophils, lymphocytes, and lysozyme resulted within the physiological range. In all farms, oxidative stress and acute phase response parameters were also within the physiological range. Our results suggest that e-GST is a very effective alarm signal to reveal "hidden" persistent contamination by β-HCH, and reasonably, by many other different dangerous pollutants.